Implementation Strategy of Criminal Policy in Directorate General of Taxes - Sihite, Irma Latifah; Silitonga, Mala Sondang; Sutrisno, Edy (Ilomata International Journal of Social Science, 2024)
The purpose of this study is to determine the aspects contributing to resistance to the implementation of criminal policies and establish implementation strategies. To have an effective and accountable criminal justice system be formed. The resistance is provided by pretrial. The impact of this mechanism is substantial because can invalidate the law enforcement that has been established over the years and must be procreated from the beginning. The methodologies used involve qualitative research. Data was obtained through document reviews, interviews, and FGD. The results revealed that the factors determining pretrial submission harmonize with Grindle's theory that can be separated into 2 (two) aspects namely content and context of policy. Furthermore, the author reveals two additional factors. The strategies are also classified into two scopes. Internally, the DGT modifies criminal policy, annotates verdicts, and strengthens implementer unit. Externally, enhances coordination with other stakeholders in the integrated criminal justice system.